2017
DOI: 10.1007/s40618-017-0772-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and implications of thyroid dysfunction induced by immune checkpoint inhibitors in real-life clinical practice: a long-term prospective study from a referral institution

Abstract: Immune checkpoint blockade is burdened by a high incidence of autoimmune thyroid dysfunction, which is often severe. Therefore, early and careful monitoring and, eventually, treatment are crucial to prevent the negative impact of thyroid dysfunction on the clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 22 publications
4
29
1
3
Order By: Relevance
“…Thyroid autoantibodies have been suggested as biomarkers to predict the development of ICI-related thyroiditis, but some studies do not support this suggestion (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). In the current study, we found that 42% of tested patients had positive TPOAb.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid autoantibodies have been suggested as biomarkers to predict the development of ICI-related thyroiditis, but some studies do not support this suggestion (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). In the current study, we found that 42% of tested patients had positive TPOAb.…”
Section: Discussionmentioning
confidence: 99%
“…Phase 3 studies of nivolumab therapy for malignant melanoma and non-squamous non-small cell lung cancer ( 4 ) have reported a frequency for hypothyroidism of 5.6–6.6% and for thyrotoxicosis of 1.4–1.9% respectively. Noteworthy, the risk of thyroid abnormalities increases substantially when patients are treated with a combination of PD-1 and CTLA-4 (cytotoxic T-lymphocyte antigen-4) inhibitors ( 14 , 15 ) or when PD-1 inhibitor follows CTLA-4 therapy, such as ipilimumab, especially when the wash-out period is <4 weeks ( 15 ). The most commonly described types of nivolumab-related thyroid dysfunction are either a transient thyrotoxic phase, which tends to resolve spontaneously and is often followed by hypothyroidism ( 11 ) or development of isolated hypothyroidism, both caused by painless thyroiditis ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thyrotoxicosis tends to occur within 6 weeks after the first administration of nivolumab. However, the time to onset of hypothyroidism ranges from 4 days to months following initiation of immunotherapy, making it very difficult to predict the occurrence time ( 11 , 12 , 14 , 15 ). Finally, it has been suggested that new occurrence of thyroid and extra-thyroid autoimmune disorders may be associated with a better treatment response to PD-1 inhibitors ( 13 , 15 ), but this finding needs to be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…В проспективном исследовании с медианой наблюдения 9 лет установлено, что субклинический гипертиреоз в анамнезе достоверно повышает относительный риск развития злокачественных новообразований любой локализации в 1,34 раза (95 % ДИ 1,06-1,69), при этом рака легких -в 2,34 раза, рака предстательной железы -в 1,97 раза, колоректального рака -в 1,34 раза [10]. Терапия противоопухолевыми и/или иммунопрепаратами, например интерлейкином 2-го типа, интерферонами [5], ингибиторами тирозинкиназы [15] и ингибиторами контрольных точек иммунного ответа [9], достаточно часто приводит к снижению функции щитовидной железы -у 14-85 % пациентов, по данным разных авторов [5,9,15]. При этом во многих исследованиях продемонстрированы увеличение уровня объективных ответов и/или улучшение показателей суррогатных маркеров выживаемости (продолжительность безрецидивного периода, продолжительность времени до прогрессирования) у онкологических больных [15].…”
Section: обсуждение полученных результатовunclassified